Functional Improvement after Taking Rehabilitation Program in Cerebellar Ataxia in a Patient with Systemic Lupus Erythematosus: a Case Report - Cha, Jun Min; Kim, Hyoung Seop (Brain & NeuroRehabilitation, 2020)
Cerebellar involvement in systemic lupus erythematosus (SLE) is rare, occurring in less than 2% of cases, with cerebellar atrophy on brain imaging even rarer. We describe a case of cerebellar atrophy in a patient with a history of SLE who underwent an intensive rehabilitation program and achieved functional improvement. A 26-years-old female with SLE felt difficult in balancing as well as dizziness and she took magnetic resonance imaging which showed cerebellar atrophy and positron emission tomography-computed tomography which showed markedly decreased signal intensity at bilateral temporal, parietal lobes, cerebellum and moderately at bilateral frontal lobes. A neurological examination showed bilateral nystagmus, intention tremor, bilateral dysmetria, and bilateral dysdiadochokinesia. Prior to the rehabilitation program, the patient's scores on the Berg Balance Scale (BBS) and Modified Barthel Index (MBI) were 4/56 and 37/100, respectively. The patient was hospitalized twice for rehabilitation treatment, which consisted of physical therapy, occupational therapy, therapeutic pool therapy, and robotic-assisted gait training. At discharge, the patient's BBS score was 9/56, and her MBI score was 46/100, and she was able to walk more than 20 m using an anterior walker. In the final 2 weeks before discharge, the patient was trained in the use of an electric wheelchair for outdoor activity.